Buddhism, politics and the limits of law : the pyrrhic constitutionalism of Sri Lanka / Benjamin Schonthal, University of Otago. - Schonthal, Benjamin, 1976- (Comparative constitutional law and policy., 2016)
It is widely assumed that a well-designed and well-implemented constitution can help ensure religious harmony in modern states. Yet how correct is this assumption? Drawing on groundbreaking research from Sri Lanka, this book argues persuasively for another possibility: when it comes to religion, relying on constitutional law may not be helpful, but harmful; constitutional practice may give way to pyrrhic constitutionalism. Written in a lucid and direct style, and aimed at both specialists and non-specialists, Buddhism, Politics and the Limits of Law explains why constitutional law has deepened, rather than diminished, conflicts over religion in Sri Lanka. Examining the roles of Buddhist monks, civil society groups, political coalitions and more, the book provides the first extended study of the legal regulation of religion in Sri Lanka as well as the first book-length analysis of the intersections of Buddhism and contemporary constitutional law.